A risk assessment of the effects of mercury on Baltic Sea, Greater North Sea and North Atlantic wildlife, fish and bivalves. (January 2021) - Dietz, Rune; Fort, Jérôme; Sonne, Christian; Albert, Céline; Bustnes, Jan Ove; Christensen, Thomas Kjær; Ciesielski, Tomasz Maciej; Danielsen, Jóhannis; Dastnai, Sam; Eens, Marcel; Erikstad, Kjell Einar; Galatius, Anders; et al.
Highlights: We investigated mercury health risks in the Baltic, Greater North Sea and North Atlantic. 23% of the marine mammals had Hg-concentrations in the High & Severe Risk Category. The corresponding percentages for birds, fish and bivalves were 2.7, 25 and 8.0% The estimated risk for Baltic populations was not higher that the bordering waters. Baltic Sea has improved with respect to mercury exposure over the last decades. Abstract: A wide range of species, including marine mammals, seabirds, birds of prey, fish and bivalves, were investigated for potential population health risks resulting from contemporary (post 2000) mercury (Hg) exposure, using novel risk thresholds based on literature and de novo contamination data. The main geographic focus is on the Baltic Sea, while data from the same species in adjacent waters, such as the Greater North Sea and North Atlantic, were included for comparative purposes. For marine mammals, 23% of the groups, each composing individuals of a specific sex and maturity from the same species in a specific study region, showed Hg-concentrations within the High Risk Category (HRC) and Severe Risk Category (SRC). The corresponding percentages for seabirds, fish and bivalves were 2.7%, 25% and 8.0%, respectively, although fish and bivalves were not represented in the SRC. Juveniles from all species showed to be at no or low risk. In comparison to the same species in the adjacent waters, i.e. the Greater North Sea and the North Atlantic, the estimated risk for Baltic populations is not considerably higher. These findings suggest that over the past few decades the Baltic Sea has improved considerably with respect to presenting Hg exposure to its local species, while it does still carry a legacy of elevated Hg levels resulting from high neighbouring industrial and agricultural activity and slow water turnover regime.